Assessment of soil development during rapid urbanization using the carbon and nitrogen stable isotope composition - Konstantinov, Alexandr O.; Konstantinova, Elizaveta Yu; Smirnov, Pavel; Minkina, Tatiana; Batalin, Georgii; Gareev, Bulat; Mingazov, Gazinur; Loiko, Sergey V. (Environmental geochemistry and health)
The proposed paper is devoted to the analysis of the urbanization effects on soil cover using physico-chemical parameters and stable isotopic signatures on the example of Tyumen. The study methods included analysis of C and N elemental and isotope (δ13C and δ15N) composition, analysis of soil physico-chemical properties and major oxides content. The results of the survey have shown that soil properties within the city limits vary significantly depending on both anthropogenic activities and geomorphological context. The urban soils of Tyumen differ from very strongly acidic with pH values down to 4.8 to strongly alkaline with pH values reaching 8.9, and from sandy loams to silty loams by texture. The study results have shown that δ13C values varied from − 33.86 to − 25.14‰ and δ15N values varied in range, especially, from − 1.66 to 13.38‰. The range of these signatures was smaller than those reported for urbanized areas in Europe and USA. The δ13C values in our case were more related to the geological and landscape parameters of the study area, rather than with urban disturbances and development of urban ecosystems. At the same time, the δ15N values probably indicate zones with increased atmospheric N deposition in the case of Tyumen. The application δ13C and δ15N is a promising tool for analysis of urban soil disturbances and functions, though the regional context should be taken into account.